Indoleamine 2, 3-Dioxygenase 1 Mediates Survival Signals in Chronic Lymphocytic Leukemia via Kynurenine/Aryl Hydrocarbon Receptor-Mediated MCL1 Modulation - Atene, Claudio Giacinto; Fiorcari, Stefania; Mesini, Nicolò; Alboni, Silvia; Martinelli, Silvia; Maccaferri, Monica; Leonardi, Giovanna; Potenza, Leonardo; Luppi, Mario; Maffei, Rossana; Marasca, Roberto (Frontiers in Immunology, 2022)
The indoleamine 2,3-dioxygenase (IDO) signaling axis, comprising the first tryptophan (Trp) catabolite L-kynurenine (Kyn) and the aryl hydrocarbon receptor (AHR), has emerged as mechanism of cancer immune evasion. Here, we investigated the functional role of IDO/Kyn/AHR axis in chronic lymphocytic leukemia (CLL). Our data show that CLL cells expressed an active form of IDO enzyme and microenvironmental stimuli can modulate positively its expression. Interferon (IFN)-γ induces IDO expression through Jak/STAT1 pathway and mediates Kyn production concomitantly with Trp consumption in CLL conditioned media, while INCB018424 (ruxolitinib), a JAK1/2 inhibitor, impaired both effects. To characterize the involvement of IDO in leukemic cells maintenance we overexpressed IDO by vector transfection measuring enhanced resistance to spontaneous apoptosis. IDO pro-survival influence was confirmed by treating CLL cells with Kyn, which mediated the increase of induced myeloid leukemia cell differentiation protein (MCL1). Conversely, AHR silencing or its blockade via CH-223191 improved apoptosis of leukemic clones and mitigated MCL1 expression. Moreover, Kyn-treated CLL cells are less affected by pro-apoptotic effect of ABT-199 (venetoclax), while CH-223191 showed synergistic/additive cytotoxicity with this drug. Lastly, targeting directly MCL1 in CLL cells with AMG-176 we abrogate the pro-survival effect of Kyn. In conclusion, our data identify IDO/Kyn/AHR signaling as a new therapeutic target for CLL, describing for the first time its role in CLL pathobiology.